Problems and Development Trends of Enterprise Informationization Management - Hu, Yuhong (Asia Pacific Economic and Management Review, 2024)
With the rapid development of information technology, enterprise information management has become an important tool to enhance the competitiveness of enterprises. Informatization management can not only improve the efficiency of work within the enterprise, but also enhance the scientific and accurate decision-making. However, in the implementation process, enterprises face many problems, such as information islands, uneven resource allocation, data security risks. These problems not only affect the process of enterprise informationization construction, but also may restrict the overall development of the enterprise. Therefore, it is of great practical significance and theoretical value to deeply explore the problems in enterprise informatization management and its development countermeasures. This paper will analyze the main problems of current enterprise informatization management and put forward corresponding development countermeasures, with a view to providing guidance for the informatization process of enterprises.